Significados e sentidos dos processos educativos vivenciados pelos jovens em situação de privação de liberdade no Centro de Atendimento Socioeducativo de Cuiabá/MT - Miranda, Kátia Aparecida da Silva Nunes (2019)
This study attempts to understand the meaning and the sense of a Socio educative Measures Program, from the arrested teenagers’ perspective, at the Socioeducational Correctional Center in Cuiabá-MT, on males’ confinement, located at Pomeri complex, institution linked to the Justice and Human Rights Secretariat (SEJUDH/MT in Portuguese). The Socio Educative Measures Program has a social and pedagogical character, that is, educational and social, in order to promote the youngsters’ personal development, so that they are able to build another life project. The questions that guides this investigation are: how do arrested teenagers signify the educational processes they experience and which expectations do they manifest for social practices on the Socioeducational Correctional Center? This study’s theoretical reference is anchored in authors such as: Freire, Fairclough and Costa, among others who share the relationship between world view, of being human and of education as theoretical fundaments. This study is of qualitative approach and the following methodological resources were used: data collection during conversation rounds. The interactions’ records happened during the workshops by using field notes organized on a field journal. Analyses’ results show, through the youngsters’ speech, the dialogical relationship and the socio educational action, the ambivalent representations of the educational processes experienced by the youngsters and the expectations they manifested. The youngsters’ speech showed how they mean the educative processes, what it is like to do time, and it shows paths which may contribute to the Socio Educational Measures Program from Mato Grosso state, at the building of alternatives so that they can approach the youngsters and to offer activities which have talks with their daily lives, their expectations and interests, with the objective to overcome and to ressignify their lives.